2018
DOI: 10.1111/cas.13894
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated microRNA‐193a‐3p is responsible for cisplatin resistance in CD44(+) gastric cancer cells

Abstract: Cisplatin is a well‐known anticancer drug used to treat various cancers. However, development of cisplatin resistance has hindered the efficiency of this drug in cancer treatment. Development of chemoresistance is known to involve many signaling pathways. Recent attention has focused on microRNAs (miRNAs) as potentially important upstream regulators in the development of chemoresistance. CD44 is one of the gastric cancer stem cell markers and plays a role in regulating self‐renewal, tumor initiation, metastasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 28 publications
1
37
0
Order By: Relevance
“…microRNAs (miRNAs) belong to small noncoding RNAs which regulate the expression of their target genes at the post-transcription level. 7 miRNAs bind to the seed sequences of the 3'-untranslated region of their target messenger RNAs (mRNAs) and mediate the degradation of corresponding mRNAs or inhibit their translation. 8 Multiple studies have reported the correlation between aberrant expression of miRNAs and cancer progression.…”
Section: Introductionmentioning
confidence: 99%
“…microRNAs (miRNAs) belong to small noncoding RNAs which regulate the expression of their target genes at the post-transcription level. 7 miRNAs bind to the seed sequences of the 3'-untranslated region of their target messenger RNAs (mRNAs) and mediate the degradation of corresponding mRNAs or inhibit their translation. 8 Multiple studies have reported the correlation between aberrant expression of miRNAs and cancer progression.…”
Section: Introductionmentioning
confidence: 99%
“…miRNA dysregulation has been reported to be valuable for GC diagnosis [30][31][32]. Recently, several studies even demonstrated the potential of miRNA in GC diagnosis and treatment [33,34]. Here, we proposed that up-regulation of miR-100-3p could inhibit proliferation and enhance apoptosis of GC cells.…”
Section: Discussionmentioning
confidence: 87%
“…MiR-421, a highly expressed miRNA in advanced gastric cancer patients, could also promote gastric cancer metastasis and DDP resistance through inhibiting E-cadherin and caspase-3 expression, in vivo and in vitro [91]. In addition, oncogenic miR-135b-5p, miR-135b, miR-17-5p, miR-193a-3p, miR-4295 and miR-3174 confer DDP resistance of gastric cancer cells through silencing Krüppel-like factor 4 (KLF4), mammalian ste20-like kinase 1 (MST1), p21, SRSF2, leucine-rich repeats and immunoglobulin-like domains 1 (LRIG1) and ARHGAP10, respectively [28,[92][93][94][95][96]. For oxaliplatin resistance, the oncogenic miR-27a has been found to enhance MDR properties by inducing MDR1/P-gp, lung resistance protein (LRP) and Bcl-2 expression in gastric cancer [97].…”
Section: Mirnas and Resistance To Platinum Drugsmentioning
confidence: 99%
“…Multiple ncRNAs acts as oncogenes or tumor suppressor genes during carcinogenesis and can also serve as diagnostic and prognostic markers of cancer patients after certain therapies [21,22]. In gastric cancer, a variety of abnormally expressed ncRNAs were identified to promote tumor progression, radioresistance, chemoresistance and targeted therapy sensitivity [23][24][25][26][27][28]. Interestingly, several miRNAs, lncRNAs and circRNAs have been found to play an essential part in gastric cancer drug resistance, especially in chemoresistance.…”
Section: Introductionmentioning
confidence: 99%